2022
DOI: 10.1590/1806-9649-2022v29e122
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Industry 4.0 technologies: an analysis of small and medium-sized companies in the state of São Paulo, Brazil

Abstract: This paper analyzed the level of adoption and compared characteristics of adopters and non-adopters of Industry 4.0 technologies. Primary data for the year 2021 were collected by means of a structured questionnaire applied to 30 small and medium-sized companies of the metallurgical sector, who operate with machining processes, in the state of São Paulo. Data were analyzed using descriptive statistical measures and correlation estimates. The technologies adopted by the companies in the sample were: Cloud Comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The study highlights what Junior and Carrer (2022) mention that businesses that have invested in specialized personnel to achieve better materials requirement planning (MRP) and enterprise resource planning (ERP) are observed in the Figure 3, where it is observed that wholesale and retail trade and services companies show more use of Industry 4.0 technologies, while companies in the manufacturing industry and transportation and transportation companies logistics to a lesser extent.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The study highlights what Junior and Carrer (2022) mention that businesses that have invested in specialized personnel to achieve better materials requirement planning (MRP) and enterprise resource planning (ERP) are observed in the Figure 3, where it is observed that wholesale and retail trade and services companies show more use of Industry 4.0 technologies, while companies in the manufacturing industry and transportation and transportation companies logistics to a lesser extent.…”
Section: Discussionmentioning
confidence: 55%
“…However, companies that have adopted industry 4.0 technologies can hire specialized personnel in Information and Communication Technologies, implement better systems for material requirements planning (MRP) and enterprise resource planning (ERP), in addition to who collaborate more actively with universities and research centers and have a better perception of their own comparative advantages (Junior, Carrer, 2022). But different authors maintain that it is important to move towards the new schemes because in the end, companies can manage to increase their competitiveness (Ynzunza et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%